2020
DOI: 10.1002/adma.202002486
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Acetylenic Polymers Grafted Cuprous Oxide as an Efficient Z‐Scheme Heterojunction for Photoelectrochemical Water Reduction

Abstract: Up to now, the field of PEC water splitting is dominated by inorganic semiconductors consisting of earth abundant elements (e.g., silicon, [7-12] metal oxides, [13-16] metal sulfides, [17,18] dichalcogenide, [19] etc.). However, the high cost and poor stability of noble metal (e.g., Pt) as cocatalysts seriously restrict the practical applications of inorganic semiconductors for the PEC hydrogen evolution reaction (HER). Compared with traditional inorganic semiconductors, organic semiconductors (e.g., graphitic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…[144][145][146] Compared with Z-scheme photocatalyst, it is considered that the reduction and oxidation reaction will take place at a lower potential for general type-II heterojunction, leading to a reduced reaction activity (Figure 11a). [122,147] Moreover, since the electron/electron or hole/hole electrostatic repulsion, it will make the photo-induced carrier migration difficult. [148] In comparison, Z-scheme heterojunction shows similar energy band alignment to the type-II heterojunction, but with a different charge carrier transfer mechanism (Figure 11b).…”
Section: Heterojunction Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…[144][145][146] Compared with Z-scheme photocatalyst, it is considered that the reduction and oxidation reaction will take place at a lower potential for general type-II heterojunction, leading to a reduced reaction activity (Figure 11a). [122,147] Moreover, since the electron/electron or hole/hole electrostatic repulsion, it will make the photo-induced carrier migration difficult. [148] In comparison, Z-scheme heterojunction shows similar energy band alignment to the type-II heterojunction, but with a different charge carrier transfer mechanism (Figure 11b).…”
Section: Heterojunction Engineeringmentioning
confidence: 99%
“…[149] The Z-scheme heterojunction can not only achieve efficient carrier separation but also retain the intrinsic photo redox potential for the oxidation/reduction reaction. [147] For instance, Lu et al reported a g-C 3 N 4 -based type-II and Z-scheme heterojunction anodes. [150] By changing the growth sequence of g-C 3 N 4 and WO 3 , different WO 3 /g-C 3 N 4 type-II heterojunction and g-C 3 N 4 /WO 3 Z-scheme heterojunction were obtained.…”
Section: Heterojunction Engineeringmentioning
confidence: 99%
“…Alternatively, Z‐scheme heterojunction has been proposed to address the problem of type II heterojunction. [ 11–13 ] Actually, it has the same band alignment with type II heterojunction, but exhibits an opposite direction of charge transfer as well as superior redox capability. [ 14,15 ] Typically, redox electron mediators such as I − /IO 3 − and Fe 2+ /Fe 3+ , as well as solid electron mediators such as Au and graphene, are required to facilitate Z‐scheme charge transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the flexible and biocompatible advantages of the natural cellulose substance, it was used as the electrode matrix for the growth of active materials for the application of PEC water splitting [80] . For instance, a conjugated acetylenic polymers (CAPs) grafted cuprous oxide (Cu 2 O) Z‐scheme heterostructured composites were in situ prepared on the Cu cellulose paper (Cu−CP), yielding the flexible CAPs/Cu 2 O/Cu−CP material [80] .…”
Section: Natural Cellulose Substances Based Materials For Photoelectrmentioning
confidence: 99%
“…Taking the flexible and biocompatible advantages of the natural cellulose substance, it was used as the electrode matrix for the growth of active materials for the application of PEC water splitting [80] . For instance, a conjugated acetylenic polymers (CAPs) grafted cuprous oxide (Cu 2 O) Z‐scheme heterostructured composites were in situ prepared on the Cu cellulose paper (Cu−CP), yielding the flexible CAPs/Cu 2 O/Cu−CP material [80] . The cellulose paper was deposited with nanocopper by a seed‐mediated growth method with gold clusters as the nucleation centers to give Cu−CP, and CAPs were in situ grown on the Cu−CP, followed with the partial oxidation of nanocopper into cuprous oxide via a simple hydrothermal process.…”
Section: Natural Cellulose Substances Based Materials For Photoelectrmentioning
confidence: 99%